The Effect of Networking, Online Sales, Offline Sales, and Training on the Trust of Cooperative Members - Welly Trilaksono; David Sukardi Kodrat (Universitas Ciputra Surabaya, 2021)
This study aims to analyze the effect of networking, online sales, offline sales, and training on the trust of members of the Karya Utama Sejati cooperative. This research is important because optimal member trust can be influenced by Networking, online sales, offline sales, and training at Koperasi Karya Utama Sejati. The sample in this study were all members of the Karya Utama Sejati cooperative, totaling 58 people. The research design used is quantitative research with a descriptive approach with an emphasis on theory testing through measurement of research variables through distributing research questionnaires. The analysis technique in this study is to use multiple linear regression analysis with the help of SPSS 20.0 software. The results showed that the networking variables had an effect on member trust, online sales had an effect on member trust, offline sales had an effect on member trust and training had an effect on the trust of members of the Karya Utama Sejati Cooperative and there was a simultaneous influence on networking, online sales, offline sales and training on trust members of the Karya Utama Sejati cooperative. The advice that can be given to the Karya Utama Sejati cooperative is to improve networking, online sales, offline sales, and training to maximize the trust of cooperative members and achieve the vision and mission of the cooperative.